2020
DOI: 10.1186/s12885-020-07605-7
|View full text |Cite
|
Sign up to set email alerts
|

Western influenced lifestyle and Kv2.1 association as predicted biomarkers for Tunisian colorectal cancer

Abstract: Background Colorectal cancer (CRC) is the third most diagnosed malignancy worldwide. The global burden is expected to increase along with ongoing westernized behaviors and lifestyle. The etiology of CRC remains elusive and most likely combines environmental and genetic factors. The Kv2.1 potassium channel encoded by KCNB1 plays a collection of roles in malignancy of cancer and may be a key factor of CRC susceptibility. Our study provides baseline association between Tunisian CRC and interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…OR10Q1 encodes for an olfactory receptor that has so far not been studied [ 117 ]. KCNB1 is a potassium voltage-gated channel that is highly expressed in the brain and has been identified as a biomarker for colorectal cancer and associated with a favorable prognosis in glioma patients [ 114 , 118 , 119 ]. Specifically, it was shown that KCNB1 regulates autophagy through the ERK signaling pathway and acts as a tumor suppressor [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…OR10Q1 encodes for an olfactory receptor that has so far not been studied [ 117 ]. KCNB1 is a potassium voltage-gated channel that is highly expressed in the brain and has been identified as a biomarker for colorectal cancer and associated with a favorable prognosis in glioma patients [ 114 , 118 , 119 ]. Specifically, it was shown that KCNB1 regulates autophagy through the ERK signaling pathway and acts as a tumor suppressor [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both the tumor characteristics and the patient conditions affect the composition of the TME, subsequently dictating disease progression, responsiveness to cancer treatments and survival prognosis. Indeed, the primary tumor’s specific genetic and epigenetic alterations, its localization (i.e., ascending, transverse or descending colon, or rectum) and the hosting organs in case of metastasis strongly impact the composition of the TME [ 19 , 20 , 21 ]. Furthermore, the patient’s genetic pre-disposition, co-morbidities, bowel pre-conditions (e.g., inflammatory bowel diseases) or lifestyle (e.g., diet, physical activities, smoking) similarly alter the TME [ 22 ].…”
Section: Overview Of Colorectal Tumor Subtypes and Associated Immune ...mentioning
confidence: 99%
“…The incidence of CRC ranks third among all cancers, whereas CRC is the second most common cause of cancer-related mortality [ 2 ]. The incidence of and mortality from CRC are increasing worldwide, with estimates to exceed 2.2 million new cases and 1.1 million deaths by 2030 [ 3 , 4 ]. While the overall incidence of CRC has declined in the United States (US), there has been a steady increase in early-onset CRC diagnosed before the age of 50 since the 1980s [ 5 ].…”
Section: Introductionmentioning
confidence: 99%